Epidemiological Characteristics and 3-year Overall Survival Outcome of Nasopharyngeal Cancer in Central Java: A Single Institution Retrospective Study - Liemiyah, Rikha; Ruspita, Dian Ayu; Naftali, Zulfikar; Muyassaroh, Muyassaroh; Farokah, Farokah (http://dharmais.co.id/, 2024)
Background: Nasopharyngeal cancer (NPC) has a high incidence and mortality rate in Indonesia, indicating poor survival outcomes. We aimed to evaluate the survival rate of NPC patients and the influence of specific underlying epidemiological characteristics on the overall survival (OS) rate of NPC patients. Methods: We reviewed the medical data from Dr. Kariadi General Hospital's clinical registry system for all newly diagnosed NPC patients between January and December 2018. We retrieved NPC patients' medical record data that met our inclusion/exclusion criteria. The overall survival rate (OS) was estimated using the Kaplan-Meier method. Between-group stratified three-year OS comparisons were conducted using weighted log-rank tests. All statistical analysis was performed in R statistical software. Results: A total of 50 NPC patients were included in the study. Majority of NPC patients were diagnosed in younger age group (58.0%). Male NPC patients dominated this study (74.0%). NPC patients were mostly diagnosed at the advanced stage (76.0%). Nonkeratinizing histology types were frequently found in the study (82.0%). NPC patients achieved a desirable better performance status (78.0%) and had no comorbidities (74.0%). Most NPC patients demonstrated a complete response to therapy (58.0%). The mean follow-up was 26.36 ± 9.5 months and drop-out rate was 18.0%. The three-year OS was 60.8%. Age, sex, stage, histological classification, performance status, comorbidity, therapy response, and therapy drop-out stratified OS did not statistically differ among NPC patients. Conclusions: We found a satisfactory NPC three-year OS. The underlying epidemiological characteristics did not significantly influence the NPC patients' three-year OS.